Rancang Bangun Sistem Informasi Administrasi Santri Pondok Pesantren Darul Musthofa Sangatta dengan Menggunakan Macro VBA Excel - Kusumah, Angga; Musa, Ibrahim; Marwanto, Marwanto; Estiningtyas, Naya; Safitri, Salsabela Nur (LPPM Universitas Bina Sarana Informatika, 2024)
The rapid advancement of information technology, particularly Microsoft Excel, facilitates the management of administrative data in educational institutions. Information systems are crucial for enhancing efficiency and effectiveness. The administration at Pondok Pesantren Darul Musthofa Sangatta is conducted manually, resulting in deficiencies such as inaccurate data, difficulties in information retrieval, limitations in student data management, and inefficient operations. The student administration information system is considered a solution to address these challenges. This system facilitates the management of student administrative data for administrators. The system is developed using the waterfall methodology, encompassing phases of requirement analysis, design, coding with VBA Macro in Microsoft Excel, testing, and maintenance. This study has produced a web-based student administration information system at Pondok Pesantren Darul Musthofa Sangatta. The system streamlines the administration of student data within the institution, conserving time, effort, and resources. Furthermore, it allows students and parents/guardians to access administrative information, including monthly payments, re-registration, and remaining funds. The system has been customized to meet the specific requirements of Pondok Pesantren Darul Musthofa Sangatta